Czas wolny: między autorefleksją a etyczną pustką - Kołodziej, Arkadiusz; Tomanek, Krzysztof (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
The problem of leisure time, as a socially significant phenomenon, has been raised since the inception of social thought. Depending on the interpretative perspective, recorded and the projected increase in the amount of leisure time, was seen as an opportunity or as a threat to the progress of the individual and society. The authors attempt is to bring theoretical dilemmas the level of the of empirical research issues. They build empirical measurement and categories such as: leisure time, self-reflection and moral sensitivity. These categories come down (narrow) previously identified theoretical inquiry into the relationship between objective and subjective dimensions of leisure, and ethical operation of the unit.